Extremely robust and post-functionalizable gold nanoparticles coated with calix[4]arenes via metal–carbon bonds. Issue 69 (25th July 2016) - Troian-Gautier, Ludovic; Valkenier, Hennie; Mattiuzzi, Alice; Jabin, Ivan; den Brande, Niko Van; Mele, Bruno Van; Hubert, Julie; Reniers, François; Bruylants, Gilles; Lagrost, Corinne; Leroux, Yann
Abstract : Gold nanoparticles stabilized with a thin layer of post-functionalizable calix[4]arenes were prepared through the reductive grafting of a calix[4]arene-tetra-diazonium salt. Abstract : Gold nanoparticles stabilized with a thin layer of post-functionalizable calix[4]arenes were prepared through the reductive grafting of a calix[4]arene-tetra-diazonium salt. These particles show exceptional stability towards extreme pH, F −, NaCl, and upon drying. Post-functionalization of the calix-layer was demonstrated, opening the way to a wide range of applications.